Особливості взаємодії концептосфер БІЗНЕС і ПОЛІТИКА в публіцистичному дискурсі: когнітивний та прагматичний аспекти - Любавська, Юлія; Lubavska, Yuliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті увага приділена виявленню особливостей взаємодії концептосфер БІЗНЕС і ПОЛІТИКА через дослідження функціонування в мові сучасної української публіцистики одиниць, які репрезентують ці концептосфери. Встановлено три типи семантичних відношень між ними: тотожності, сукупності та зв’язку, – що можуть виявлятися в статичному та динамічному аспектах. The article is devoted to the issue of the interaction of the concepts BUSSINES and POLITICS in modern Ukrainian journalistic discourse. As a result of studying in journalistic texts the function of units representing these concepts, were established three types of semantic relations between these cognitive structures: identity, aggregate and connection. It was traced the relationship of identity may occur in static and dynamic aspects. There are regularities related to the fact that in the context with the relation of identity between lexical reprezentantatives of the concepts predicative relationship is established, based on the identification, and in the context with the semantics of aggregate and connection the main is figurative implementation of relations. Also the pragmatic component of the interaction of these concepts is traced, types of partial evaluations related to this process are defined. Statements that verbalize the relationship between theses concepts are interpreted as objectivators of social realities and ideas that reveal the content of concepts BUSSINES and POLITICS in modern Ukrainian linguistic worldview.
Features of Interaction of Concept Spheres BUSSINES and POLITICS in the Journalistic Discourse: Cognitive and Pragmatic Aspects.
Keywords: концептосфера; оцінка; суб’єкт оцінки; типи часткових оцінок; конотація; мова публіцистики; concept sphere; evaluation; the subject of evaluation; types of partial evaluation; connotation; journalistic language